TEACHING WRITING USING PREPARE ORGANIZE WRITING EVALUATE RETHINK STRATEGY AT THE EIGHT GRADE OF MTs MAHWIL UMMIYAH MUARA LAPA DAYA DUNGKEK SUMENEP IN THE ACADEMIC YEAR OF 2019/2020 - Ummul Khoiroh; Haris Supratno; Ria Kamilah Agustina (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2021)
Writing learning using P.O.W.E.R. strategy that occurs in the eight class of MTs Mahwil Ummiyah make innovative and inspiring learning, the students innovatively to creative study and independent, the strategy is involving students to evaluate and revise independently who crated students in writing. The goal is the POWER method to be achieved in the writing learning effectively, to descript the students of result in the writing learning using the POWER method. The technique data analysis data reduction the researcher observe in the field, data display to descript the result, conclusion is the verification. The result of this research can be seen in the 4 cycles of learning process. 20,5% is the students learning result from first cycle in the second cycles out 72% in the third cycles 85% in the fourth 91%. Can conclude that students writing learning was drastic increase. this shows that the learning process using the POWER method of students in MTs Mahwil Ummiyah successfully. Keyword: Teaching Writing Using P.O.W.E.R Method